2016
DOI: 10.1021/acs.chemmater.6b01929
|View full text |Cite
|
Sign up to set email alerts
|

Unipolar Electron Transport Polymers: A Thiazole Based All-Electron Acceptor Approach

Abstract: Experimental details, synthesis and analysis of the monomers and polymers, additional figures, and additional characterization data (PDF).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
85
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 47 publications
3
85
0
Order By: Relevance
“…From a synthetic point of view, state‐of‐the‐art Stille or Suzuki polycondensations have been mostly applied to prepare BTz‐, and also NDI‐based, polymers. These synthetic transformations are currently being replaced by in many ways more attractive C‐H functionalization strategies.…”
Section: Introductionmentioning
confidence: 99%
“…From a synthetic point of view, state‐of‐the‐art Stille or Suzuki polycondensations have been mostly applied to prepare BTz‐, and also NDI‐based, polymers. These synthetic transformations are currently being replaced by in many ways more attractive C‐H functionalization strategies.…”
Section: Introductionmentioning
confidence: 99%
“…[4,10] Thec ombination of two imide-functionalized arenes,NDI and TPD,was selected due to their strong electron acceptor characteristics and deep HOMO levels,w hich could facilitate the electron transport and efficiently block the hole injection, respectively. [4,10] Thec ombination of two imide-functionalized arenes,NDI and TPD,was selected due to their strong electron acceptor characteristics and deep HOMO levels,w hich could facilitate the electron transport and efficiently block the hole injection, respectively.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…This polymer showed promising unipolar n-type charge transport properties with the m e of 0.22 cm 2 V À1 s À1 (Figure 1a left). [4] Very recently,G uo et al found that the all-acceptor homopolymers PDTzTI and PBTI1, consisting of only the bithiazolothienyl tetracarboxydiimide (DTzTI) unit and bithiophene imide (BTI), respectively,e xhibited unipolar n-type charge transport properties with the remarkable m e up to 3.71 cm 2 V À1 s À1 (Figure 1a right). [4] Very recently,G uo et al found that the all-acceptor homopolymers PDTzTI and PBTI1, consisting of only the bithiazolothienyl tetracarboxydiimide (DTzTI) unit and bithiophene imide (BTI), respectively,e xhibited unipolar n-type charge transport properties with the remarkable m e up to 3.71 cm 2 V À1 s À1 (Figure 1a right).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations